2020
DOI: 10.3390/foods9101487
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Healthy Oils for Improving the Nutritional Characteristics of Dry-Fermented Deer Sausage

Abstract: The influence of partial replacement of animal fat by healthy oils on composition, physicochemical, volatile, and sensory properties of dry-fermented deer sausage was evaluated. Four different batches were manufactured: the control was formulated with animal fat (18.2%), while in the reformulated batches the 50% of animal fat was substituted by olive, canola, and soy oil emulsions immobilized in Prosella gel. The reformulation resulted in a decrease of moisture and fat contents and an increase of protein and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 63 publications
5
28
0
1
Order By: Relevance
“…Finally, three different papers reported results about the use of hydrogels in the reformulation of dry-fermented sausages (fuet, dry-fermented sausage, and dry-fermented deer sausage). These strategies included a mixture of olive–chia oils immobilized in soy protein/gelatin hydrogel (80% of fat replacement) [ 26 ], the use of lecithin/gelatin/inulin based hydrogels with linseed oil (64% fat replacement) [ 59 ], and the application of alginate-based hydrogels with three different oils (olive oil, canola oil, or soy oil) for 50% of fat replacement in sausages [ 60 ]. The reformulation in all studies resulted in a significant increase of protein, MUFA, and/or PUFA, while increasing moisture in two out of three sausages [ 26 , 59 ] and decreasing this parameter in the deer sausages [ 60 ].…”
Section: Incorporation Of Lipid Bio-based Ingredients Into Meat Symentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, three different papers reported results about the use of hydrogels in the reformulation of dry-fermented sausages (fuet, dry-fermented sausage, and dry-fermented deer sausage). These strategies included a mixture of olive–chia oils immobilized in soy protein/gelatin hydrogel (80% of fat replacement) [ 26 ], the use of lecithin/gelatin/inulin based hydrogels with linseed oil (64% fat replacement) [ 59 ], and the application of alginate-based hydrogels with three different oils (olive oil, canola oil, or soy oil) for 50% of fat replacement in sausages [ 60 ]. The reformulation in all studies resulted in a significant increase of protein, MUFA, and/or PUFA, while increasing moisture in two out of three sausages [ 26 , 59 ] and decreasing this parameter in the deer sausages [ 60 ].…”
Section: Incorporation Of Lipid Bio-based Ingredients Into Meat Symentioning
confidence: 99%
“…In all cases, the total fat and the SFA content decreased, which resulted in a significant improvement of nutritional indices (n-6/n-3 and PUFA/SFA). In fuet, the inclusion of hydrogels increased L* and b* color values [ 26 ], while in the other two sausages [ 59 , 60 ] the reformulation reduced these two parameters. The authors found that the use of the olive–chia oil mixture increased both lipid oxidation and lipid-derived volatiles in reformulated fuets [ 26 ].…”
Section: Incorporation Of Lipid Bio-based Ingredients Into Meat Symentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, consumers, aware of the implications that diet has on health and well-being, demand nutritious and safe products that have a benefit to their health [55]. The use of bioactive compounds for the reformulation of traditional food products allows for the transformation of these products into functional foods.…”
Section: Potential Use Of Beetroot For the Development Of Functional mentioning
confidence: 99%
“…Consumers perceive meat products as an important source of dietary fat [3,4]. In addition, this fat is usually an important source of saturated fatty acids and cholesterol [2,5,6]. Therefore the meat industry has been looking for strategies to reduce or modify the lipid profile of said products, with the aim of offering consumers healthy products without compromising their sensory characteristics or stability [2].…”
Section: Introductionmentioning
confidence: 99%